Peran Kelembagaan Komunitas Adat Buluttana pada Pengelolaan Agribisnis Tanaman Padi ( Ozyva sativa. L) di Kabupaten Gowa, Sulawesi Selatan - Fitrianti, Fitri; Zain, Majdah M; Ibrahim, Helda; Yunus, Awaluddin (Jurnal KIRANA, 2025)
This study aims to analyze the institutional role of the Buluttana indigenous community in rice farming (Oryza sativa) in Gowa Regency, South Sulawesi. Qualitative data analysis method by studying or analyzing and describing the role of institutions in increasing rice productivity. This study uses the Likert scale method, which is a method used to measure a person's attitude, opinion, or perception of a statement. The sample in the study was taken using the purposive sampling method or by taking samples intentionally. The number of samples taken was 10% of the population or 60 farmers. The results of the study based on the filling of the Likert Scale instrument showed that the involvement of indigenous peoples was very high with an index of 94.3%; the role of preserving Buluttana indigenous culture is very high in rice farming with an index of 93.6%; the role of teaching traditions is very high in rice farming with an index of 92%; the role of conflict resolution and mediation of Buluttana customs is very high with an index of 92.3%; the role of natural resource management by the Buluttana custom is very high with an index of 91.3% and the role of the Buluttana custom community in the relationship between farmers and the government (stakeholders) is very high in rice farming efforts with an index interpretation of 90.3%. The conclusion of this study is that customary institutions have been proven to have a major influence on community participation in agricultural activities, maintaining the sustainability of local culture, passing down agricultural traditions from generation to generation, conflict resolution and mediation, regulating natural resource management, and being an effective liaison between farmers and the government.